Controlling the velocity of air in the working section and in the body of a wind tunnel - Al Wahaibi, Mohammed Saif (2015)
This dissertation deals with the multivariable control of an aircraft wind tunnel in order to find the simplest and most economical way of controlling the flow of air in the working section of a wind tunnel model. This model has two inputs, which are the fan motor and the ventilator vanes, and two outputs, which are the velocities in the form of multi input-output model. The comparison of the control methods used will be based on the assessment of the energy dissipated and the dynamic performance. The preferred control method of Least Effort Regulation will be assessed and related to the decoupling compensator method. Block diagrams of both methods and their plots will be included and step response transients and random noise assessment will be presented. The conclusion will state that the least effort control will be the best choice and a preferred method in terms of performance, economy, and energy dissipation from the results that are achieved.